Hybridized Surviving: The Diaspora Narratives of Joseph, Esther, and Daniel - Kolia, Brian Fiu (Religions, 2022)
There are a number of challenges faced by diasporic people, yet they all seem to be connected to one major issue: "identity". Their narratives are built on questions surrounding who they are, when they are no longer living in/on their home/land. As they migrate to foreign lands, their notions of identity become clouded, and quite often they struggle to "belong". Second-generation people could be heard asking: "Where do we belong?" "The lands our parents came from?" "Or the lands we now live?" "Is it both? Or is it neither?" "Do we even know who we are? How do we fit in? How do we survive?" The aim of this essay is to highlight the issue of diasporic identity in the narratives of three biblical migrants: Joseph, Esther, and Daniel. The purposes of these biblical accounts seem to reflect the ambivalence of diasporic existence, where they can achieve success but also experience adversity. Yet these narratives also deal with how identity is problematized in diasporic contexts. I will be engaging these narratives in conversation with my own story, in a bid to view alternative understandings and constructs of diasporic existence, particularly for second-generation migrants within religious communities. Furthermore, the hope is that a re-reading of these narratives may generate alternative theological considerations in light of the struggles of second-generation migrants.